Correlation of Point B and Lymph Node Dose in 3D-Planned High-Dose-Rate Cervical Cancer Brachytherapy - Lee, Larissa J. (2009)
PURPOSE: To compare the HDR point B to pelvic lymph node dose using 3D-planned brachytherapy for cervical cancer. MATERIALS AND METHODS: Patients with FIGO Stage IB-IIIB cervical cancer received 70 tandem HDR applications using CT-based treatment planning. The obturator, external and internal iliac lymph nodes (LN) were contoured. Per fraction (PF) and combined fraction (CF) right (R), left (L), and bilateral (Bil) nodal doses were analyzed. Point B dose was compared with LN dose-volume histogram (DVH) parameters by a paired t-test and Pearson correlation coefficients. RESULTS: The mean PF and CF doses to point B were R 1.40 Gy ±0.14 (CF: 7 Gy), L 1.43 ±0.15 (CF: 7.15 Gy), and Bil 1.41 ±0.15 (CF: 7.05 Gy). The correlation coefficients between point B and the D100, D90, D50, D2cc, D1cc, and D0.1cc LN were all less than 0.7. Only the D2cc to the obturator and the D0.1cc to the external iliac nodes were not significantly different from the point B dose. Significant differences between R and L nodal DVHs were seen, likely related to tandem deviation from irregular tumor anatomy. CONCLUSIONS: With HDR brachytherapy for cervical cancer, the per fraction nodal dose approximates a dose equivalent to teletherapy. Point B is a poor surrogate for dose to specific nodal groups. 3D-defined nodal contours during brachytherapy provide a more accurate reflection of delivered dose, and should be part of comprehensive planning of the total dose to the pelvic nodes, particularly when there is evidence of pathologic involvement of nodes.